(3OjhGf LQjQs - (3LQjQ Hf YWjI Hf MPjaI GdNWaj GdjQHhYj GdJejej,J (B110 (3g` s ((3jGbhJ GdeSJYUej s)
(3ChdgG (B:s
(3bGd LQjQ jgLh GdCNWd Mj GdZOGI HQGeI GdCWdGdG QSeG JMed Cgdg aCMGdG s
(3BNQgG (B:s
(3bUjOI HGFjI eWdYgG(B: (3dh cfJ aj ZeOGf Ch aj YeGjI EPG dG JCfj ef QHjYI QGcH s
(3GdfSNI HgG MhGTs
(3fSNI KGfjI HQhGjI CHj SYjO GdMSf Hf GdMSjf GdScQj Yf eMeO Hf MHjH Yf eMeO Hf RjGO GdCYQGHj hYeGQI Hf Ybjd Hf HdGd Hf LQjQs
(3hQO CjVkG JMJ Qbe (B831(3, (B832(3, (B877(3, (B1020(3, (B1021(3, (B1022(3, (B2399s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B111s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B65 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B782s
Keywords: (3GdCOHs